2020
DOI: 10.3390/microorganisms8030373
|View full text |Cite
|
Sign up to set email alerts
|

The Nature and Extent of Plasmid Variation in Chlamydia trachomatis

Abstract: Chlamydia trachomatis is an obligate intracellular pathogen of humans, causing both the sexually transmitted infection, chlamydia, and the most common cause of infectious blindness, trachoma. The majority of sequenced C. trachomatis clinical isolates carry a 7.5-Kb plasmid, and it is becoming increasingly evident that this is a key determinant of pathogenicity. The discovery of the Swedish New Variant and the more recent Finnish variant highlight the importance of understanding the natural extent of variation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 90 publications
(167 reference statements)
0
15
0
3
Order By: Relevance
“… 29 Most human and animal pathogens classified in the family Chlamydiaceae carry a conserved 7.5 kb plasmid with eight plasmid encoded proteins, referred to as plasmid glycoproteins Pgp1–8. 30 , 31 , 32 , 33 These low copy number plasmids 34 represent an important virulence factor in the natural host. 35 , 36 , 37 , 38 Accumulating evidence indicates coevolution of chlamydial plasmids and chromosomes within the family Chlamydiaceae.…”
Section: Introductionmentioning
confidence: 99%
“… 29 Most human and animal pathogens classified in the family Chlamydiaceae carry a conserved 7.5 kb plasmid with eight plasmid encoded proteins, referred to as plasmid glycoproteins Pgp1–8. 30 , 31 , 32 , 33 These low copy number plasmids 34 represent an important virulence factor in the natural host. 35 , 36 , 37 , 38 Accumulating evidence indicates coevolution of chlamydial plasmids and chromosomes within the family Chlamydiaceae.…”
Section: Introductionmentioning
confidence: 99%
“…This analysis conforms with the previously studied hypothesis that identified CDS5 (virulence associated protein) as the most polymorphic gene within C. trachomatis with a p-distance of 0.008 [30]. However, the same study identified CDS2 as the most conserved and least diverse gene on the plasmid with only 11 allelic variations within the C. trachomatis species [30], whilst a more recent study identified CDS6 as the most conserved plasmid gene in C. trachomatis across a much larger sample set (but CDS2 was the most conserved at the amino acid level) [27] Our calculations gave a p-distance of 0.254 and SE = 0.008 for CDS2, which was considerably higher compared to CDS4 with a p-distance of 0.181. One might argue that this difference could be due to two of the present species (C. avium 10DC88 and C. gallinacea 08-1274/3) possessing mutations.…”
Section: Discussionmentioning
confidence: 92%
“…Further studies established that these plasmids are present in most strains of C. trachomatis. The plasmid is highly conserved, with an intraspecific variation of around 3% [27]. Large-scale deletions or rearrangements of the plasmid are therefore rare [27,28], but in 2006 a new strain was described that evaded PCR detection due to a single large deletion in CDS1 of its plasmid [29].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although our "in-house" LISA used one Pgp3 protein from serovar E of C. trachomatis, it does show comparable performance with the commercial Mikrogen ELISA, which uses multiple C. trachomatis antigens (MOMP, TARP, and CPAF). Of note, Jones et al (2020) recently reported the variation of Pgp3 protein with a genetic distance of 0.013 at the amino acid level among different C. trachomatis serovars. However, the small genetic distance of Pgp3 gene and the corresponding 98.7% sequence identity maintains a 94% probability of cross-reactivity within C. trachomatis species according to the formula "P cross = e (−9.4153 + 0.123223 × percent sequence identity) /[1 + e (−9.4153 + 0.123223 × percent sequence identity) ] reported by Rahman et al (2015Rahman et al ( , 2018b.…”
Section: Discussionmentioning
confidence: 99%